2014
DOI: 10.1017/s0263034614000482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of electron density of states in laser-superposed channeling regime

Abstract: We present low-dimensional functionalization and characterization of electron density of states using highly correlated/ precisely guided proton beam trajectories and a silicon nanocrystal as a target, representing at a same time a versatile nanolaser technique capable for coherent control of atomic quantum states and for scanning the interior of an atom with resolution comparable to 10% of the Bohr radius.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Each interval in path integral relations (6) and (7) must have one d and one h factor in order to limit the possible paths and maintain causality. h factor attributes the specific electron loss [7,20] arising from the multiple scattering effect and collisions with valence electrons, as following…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each interval in path integral relations (6) and (7) must have one d and one h factor in order to limit the possible paths and maintain causality. h factor attributes the specific electron loss [7,20] arising from the multiple scattering effect and collisions with valence electrons, as following…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, coherence being the central part of the interference phenomena [3], produces phase summing instantaneously identifying an interferential multiplier in the scattering cross-section, which leads to appearance of coherent peaks when the transferred momentum of the energetic particle coincides, i.e., when it is in resonance, with one of the reciprocal lattice vectors [4]. Experimental and theoretical studies [5] have revealed appearances of similar coherent peaks in the orientation-dependant backscattering yield investigations and confirmed that collisions of energetic particles with crystal surfaces [6] can provide information about binary interactions involving outer-shell electrons [7]. By selecting specific backscattered particles whose energy losses are correlated with a particular surface atomic species, it is possible to determine binary collision produced trajectories, isolating in that way cases when the energetic particle is scattered off a single surface atom from those cases where multiple collisions or penetration into the solid occur.…”
mentioning
confidence: 99%